Assistentes de alunos: quem são esses profissionais que atuam na educação profissional técnica de nível médio? - Oliveira, Rosenira Monteiro da Costa (2020)
This research discusses the perceptions of the professional practice of the Students' Assistants in the Integrated Secondary School-EMI, identifying their attributions and their educational work in the EPTNM, focused on line 02 of the Post-Graduation Program in Professional and Technological Education (PROFEPT) that deals with the "Organization and Memories of Educational Spaces in EPT" directed to Macroproject 06, regarding the "Organization of Educational Spaces in EPT". It gives as a problem the following question: How has the educational work of the Student Assistant been constructed in the context of the Technical Professional Education of Medium Level in the Integrated Modality? The general objective was to investigate the work of the Student Assistant in the context of Technical High School Vocational Education in the Integrated Mode. Studying the meanings attributed by the student assistants to their practice, qualitative research was used as a methodological procedure using the printed form and the semi-structured interview as a technique, applied to a group of eight student's assistant from the Federal Institute of Education, Science, and Technology off Amazonas - Campus Manaus Centro (IFAM-CMC) that made it possible to survey information essential to the process of objectifying the concepts about their professional practice. Besides the theoretical references, documents, theses, and other sources were collected and analyzed, which we used for the elaboration of this work. Summing up, it was verified that the understanding of the meaning and the challenges of the professional practice of the Student Assistants, conditioned to factors, positive and negative, reported by the professionals and analyzed as constitutive of their profession: a dichotomy between their attributions and the objectives of EPT; challenge of affirming the work as an educational principle before the work submitted to the logic of the market; devaluation and lack of recognition of the profession by the institution. Finally, as a perspective of overcoming these obstacles, the pedagogical product is presented - materialized in a Digital Booklet and constitutive of the dissertation - given the promotion of spaces for reflection and educational actions under the rationale of work as an educational principle, essential to the omnilateral human formation.